Review of factors affecting limb salvage surgery in civilian population - Ali, Ismail; Abdul Rahman, Mohd Norhisham Azmi; Mohd Yusof, Nazri; Othman, Ahmad Faidzal (2014)
Arterial injuries to extremities account for 50% of all trauma cases. Extremities injuries can be quite challenging to the surgeon due to the limited time for intervention. Management of traumatic limb ischemia has tremendously evolved from simple ligation of damaged vessel during World War I and II which resulted in amputation rate of 70%. Nowadays after dramatic improvement in management the limb salvage rates reaches up to 83.8%.